Web and information security - Ferrari Elena; Thuraisingham Bhavani (Hershey IRM Press, 2006)
This book consists of a collection of papers written by leading experts in the field that describe state-of-the-art topics pertaining to Web and information systems security. In particular, security for the semantic Web, privacy, security policy manageme
Keywords: Computer network; Computer security; Security measures; Semantic web; Web sites